The roles of socioeconomic status and justice perceptions in social science study programs - Dietrich, Heike (2018)
Research indicates that SES is relevant for students’ educational decisions and outcomes and that people’s justice perceptions are important for their performance and behavior. However, in Germany, the role of SES has received little attention in the area of higher education. In addition, justice perceptions are often not considered in higher educational contexts. The current dissertation tried to fill both voids—by seeking to extend the knowledge and understanding of the roles of students’ SES and students’ justice perceptions in social science study programs. The first study in this dissertation addressed the question of whether first-semester social science students’ objective SES would be related to the characteristics students brought to their study programs. The second study addressed the questions of whether psychology students’ objective SES would predict their academic achievement and whether psychology students’ subjective SES would explain additional variance beyond objective SES. In addition, different measures of subjective SES were investigated. The third study addressed the question of whether psychology students’ justice perceptions could be assessed with a questionnaire that originated in organizational psychology. In addition, associations between students’ justice perceptions and student characteristics were investigated. The main results of the studies revealed that objective SES was associated with only some of the characteristics students brought to their studies (e.g., school grades, number of hours spent working side jobs) but not others (e.g., intelligence). In addition, objective SES and most measures of subjective SES did not predict psychology students’ academic achievement—with the exception of a trinity of measures of subjective SES that disentangled classical aspects of SES and that were adapted to higher education. Finally, to a large extent, it appears to be possible to assess students’ justice perceptions with a questionnaire from organizational psychology. These and additional findings are discussed and placed in a broader context, recommendations for future research are derived, and conclusions are drawn.
Keywords: Hochschulschrift